Modified Cement Paste using Micro-fine POFA under Ammonium Nitrate condition - Tasnim, Sadia (Curtin University, 2017)
The aim of this research is to study the performance of fine palm oil fuel ash (POFA) to control ammonium nitrate attack in cement paste. The mechanical, durability and micro-structural properties of the modified cement paste in room temperature and in ammonium nitrate condition was studied. Based on the test results, it was observed that, 20% POFA based paste provided better resistance in room temperature and in ammonium nitrate solution.